Eight Million Years of Satellite DNA Evolution in Grasshoppers of the Genus Schistocerca Illuminate the Ins and Outs of the Library Hypothesis - Palacios-Gimenez, Octavio M; Milani, Diogo [UNESP]; Song, Hojun; Marti, Dardo A; López-León, Maria D; Ruiz-Ruano, Francisco J; Camacho, Juan Pedro M; Cabral-De-Mello, Diogo C [UNESP]; O'Neill, Rachel (Oxford University Press (OUP), 2020)
Satellite DNA (satDNA) is an abundant class of tandemly repeated noncoding sequences, showing high rate of change in sequence, abundance, and physical location. However, the mechanisms promoting these changes are still controversial. The library model was put forward to explain the conservation of some satDNAs for long periods, predicting that related species share a common collection of satDNAs, which mostly experience quantitative changes. Here, we tested the library model by analyzing three satDNAs in ten species of Schistocerca grasshoppers. This group represents a valuable material because it diversified during the last 7.9 Myr across the American continent from the African desert locust (Schistocerca gregaria), and this thus illuminates the direction of evolutionary changes. By combining bioinformatic and cytogenetic, we tested whether these three satDNA families found in S. gregaria are also present in nine American species, and whether differential gains and/or losses have occurred in the lineages. We found that the three satDNAs are present in all species but display remarkable interspecies differences in their abundance and sequences while being highly consistent with genus phylogeny. The number of chromosomal loci where satDNA is present was also consistent with phylogeny for two satDNA families but not for the other. Our results suggest eminently chance events for satDNA evolution. Several evolutionary trends clearly imply either massive amplifications or contractions, thus closely fitting the library model prediction that changes are mostly quantitative. Finally, we found that satDNA amplifications or contractions may influence the evolution of monomer consensus sequences and by chance playing a major role in driftlike dynamics.
Keywords: chromosomal evolution; genome organization; repetitive DNA; tandem repeats